Pembelajaran Tembang Kerakyatan Banyumasan di Institut Seni Indonesia Surakarta - Andika Agustino Wella Mahendra; Indar Sabri; Setyo Yanuartati; Siswati Siswati (Universitas Hamzanwadi, 2025)
The learning of Banyumasan folk songs in art colleges represents an important effort in preserving local culture. Currently, the preservation of folk songs faces significant challenges due to the lack of educational media and the low interest among younger generations. Given the limited knowledge in this area, it is essential to incorporate this material into the curriculum of the Indonesian Institute of the Arts (ISI) Surakarta. This learning process is expected to broaden students' knowledge and enhance their competencies in performing folk songs. This study aims to examine the learning process of Banyumasan folk songs at ISI Surakarta, focusing on teaching strategies, learning materials, the role of lecturers, as well as the challenges and contributions of this educational approach to local cultural preservation. The research method employed is qualitative descriptive, using data collection techniques such as observation, in-depth interviews, and documentation. The findings show that the learning of Banyumasan folk songs has been integrated into the curriculum through contextual, collaborative, and project-based approaches. The study also explores the methods used by instructors to help students understand and perform the songs effectively. This research highlights the strategic role of arts education in the revitalization and preservation of Banyumasan culture. These findings are expected to serve as a reference for the development of curriculum and learning strategies for Banyumasan folk songs in higher education institutions of the arts.